Causes of climate change: a neglected dimension - Adam, Umar Musa; Sanusi, Zainal Abidin; Suleiman, Hassan (IIUM Press, 2024)
Climate change is one of the most disturbing challenges faced by humankind due to the profound threat it poses to human life and livelihood, affecting almost every aspect of life negatively. A comprehensive grasp of the causes of climate change is imperative for effective mitigation strategies. However, the most prevalent causes of climate change are advanced within the Western scientific perspective. This article aims to provide a cross-cultural comparison between the Islāmic and Western scientific perspectives on the causes of climate change. Based on the review of scientific literature and other relevant documents, the article argues that both the Islāmic and the secular perspectives on the impacts of climate change are in accord. However, the causes of climate change extend beyond the material scientific explanation. The mischief and sins of human beings on earth are fundamental causes that should not be ignored. The article concludes that mitigation efforts will remain one-sided unless these two dimensions of human activities are perceived as the causes of climate change. ***** Perubahan iklim adalah salah satu cabaran yang paling membimbangkan yang perlu dihadapi oleh manusia. Ini kerana perubahan iklim dapat memberikan ancaman serius kepada kehidupan dan mata pencarian manusia, bahkan ia hampir menjejaskan semua aspek kehidupan secara negatif. Pemahaman menyeluruh tentang punca perubahan iklim adalah penting untuk strategi mitigasi yang berkesan. Walau bagaimanapun, punca perubahan iklim yang paling popular adalah kemajuan mengikut perspektif saintifik Barat. Artikel ini bertujuan untuk menyediakan perbandingan silang budaya antara perspektif sains Islam dan Barat tentang punca perubahan iklim. Hujah menunjukkan bahawa walaupun kedua-dua perspektif Islam dan sekular terhadap kesan daripada perubahan iklim adalah selaras namun punca perubahan iklim adalah melampaui penerangan saintifik yang material. Kerosakan dan dosa manusia di muka bumi juga menjadi asbab utama yang tidak boleh diabaikan. Artikel ini menyimpulkan bahawa usaha mitigasi akan kekal berat sebelah melainkan kedua-dua dimensi aktiviti manusia ini diambil kira sebagai punca kepada perubahan iklim.